2018
DOI: 10.7196/samj.2018.v108i12.13679
|View full text |Cite
|
Sign up to set email alerts
|

Alternative modalities being promoted for breast screening

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Ghartey et al [28] screened 2204 women in Ghana and reported a sensitivity of 92.3% with the device as compared to 73% with CBE; however, specificity remains unreported (Figure5a-c). We agree with other authors [37,38] that there is a need for more clinical trials before using the transillumination method as a rapid diagnostic tool as it does offer a potentially accurate tool that is inexpensive and very easy to use. The varying sensitivity showcases the need for the rapid diagnostic tool which can delineate between normal and abnormal breast based on biomarkers such as hemoglobin, lipids, collagen, water and tissue properties such as absorption coefficient, reduced scattering coefficient, oxygen saturation, and tissue oxygenation index.…”
Section: Molecular Level Information High Sensitivitysupporting
confidence: 86%
See 1 more Smart Citation
“…Ghartey et al [28] screened 2204 women in Ghana and reported a sensitivity of 92.3% with the device as compared to 73% with CBE; however, specificity remains unreported (Figure5a-c). We agree with other authors [37,38] that there is a need for more clinical trials before using the transillumination method as a rapid diagnostic tool as it does offer a potentially accurate tool that is inexpensive and very easy to use. The varying sensitivity showcases the need for the rapid diagnostic tool which can delineate between normal and abnormal breast based on biomarkers such as hemoglobin, lipids, collagen, water and tissue properties such as absorption coefficient, reduced scattering coefficient, oxygen saturation, and tissue oxygenation index.…”
Section: Molecular Level Information High Sensitivitysupporting
confidence: 86%
“…Transillumination imaging has been studied using a commercial tool such as Breastlight [29,30] and has been found to have varying sensitivities between 60% and 93% for breast cancer detection, primarily due to the dependency on the skill of the clinician to visually analyze the transillumination images. [28,[30][31][32][33][34][35][36] Mehnati et al [37] and Edge et al [38] critically review the transillumination imaging for breast screening and recommended performing more clinical trials.…”
Section: Introductionmentioning
confidence: 99%